Green Collaboration for Sustainable Living: Learning, Empowerment, and Prosperity in Sukadamai village, Cikupa District, Tangerang - Sadi, Sumardi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Green collaboration emphasizes cross-sector cooperation for environmental, economic, and social sustainability. This article explores the